The Venture Capital Industry in Europe - Schertler, Andrea (Palgrave Macmillan UK, 2006)
By analyzing venture capital industries, this book substantially adds to the understanding of Europe's venture capital industries. It discusses the microeconomics of fund raising, investment and exiting behaviour of venture capital companies and relates the microeconomics of venture capital finance to the industry features in European countries
Keywords: Business; Business enterprises / Finance; New business enterprises; Corporations / Finance; International economics